Water management and mulching on rice production under aerobic condition - Espino, Armando N., Jr (Philippine agricultural mechanization journal)
The study aimed to establish proper water management using rice straw as mulching material on rice production under aerobic condition. The study was conducted at the Water Resources Management Center Techno-demo and Research Farm, Central Luzon State University, Science City of Muñoz, Nueva Ecija from January 2009 to June 2009. The experiment was laid out following the split-split plot in randomized complete block design, with irrigation interval as the main plot : W1=5 days irrigation interval and W2 = 7 days irrigation interval; irrigation methods as the sub-plots : 11=basin, 12 furrow and 13=sprinkler; and soil cover as the sub-sub plots : M1=bare soil and M2=rice straw. For basin and sprinkler irrigation methods, rows were constructed at 25 cm apart using lithao. Furrows were established at 75 cm apart with three plant rows in between furrows. The APO variety (PSBRC-9) was used in this study. Seeds were hand-dibbed 1.5 cm deep and covered with soil. Seed density was 60 kg ha-1. After sowing, rice straw mulch was laid into the plot at a rate of 5 tons ha-1. Water is one of the basic needs of plants to grow especially in rice production system. Although aerobic rice, specifically Apo variety, can be grown with less water compared to lowland rice production, results showed that increasing the amount of water applied can increased the height of the crop. However, irrigating aerobic rice in furrow at five days interval can increase the plant height significantly compared to basin and sprinkler irrigation systems. Also, it can increase the rice yield of about 0.2 to 0.5 tons per hectare. Based on the results of the study, number of tillers and number of panicles were not affected by the water treatments, straw mulch and their combinations. However, percentage of filled spikelets can be reduced with insufficient amount of water available during the panicle initiation stage of the crops. Due to continuous rainfall during the conduct of the study from flowering stage to maturity of the crops, the effect of water treatments during these stages were not properly established. Results of the study showed that application of rice straw as mulch showed plant height reduction, however, it increased rice yield compared to bare soil. This proved that organic mulching affects the growth and yield of the crops by consuming and contributing nutrient during and after decomposition. During the conduct of the study, rainfall occurred from the onset of flowering stage to maturity and it contributes more than half of the amount of irrigation water. This circumstance greatly influenced the computation of water productivity. However, considering only the amount of water irrigated, more than 20 percent of water can be saved by using furrow irrigation method compared to basin method of irrigation. Likewise, more than 60 percent can be saved by using the sprinkler or LESA system.